PRAGMATIC ANALYSIS OF LANGUAGE ELEMENTS IN DETECTIVE FICTION - Gulnorakhon Niyazova (Scholar Express Journal, 2023)
In this article, the researcher deals with the study of the language of detective fiction in the socio-pragmatic and gender aspects that would give important results in linguistics. The pragmatic features of the language of detective fiction in two languages were analyzed and discussed. The basis of the article is the analysis of the linguistic elements of detective fiction and the clarification of ideas on specific examples. Analysis and study of the language features of detective stories requires special attention to the pragmatic features of the language of detective stories. In this case, the context of the detective work is taken as the object of pragmatic analysis, and in the process of analysis, certain linguistic characteristic features of the text of the fiction are studied
Keywords: pragmatic environment; detective genre; pragmatic analysis; context of detective production